'We're doing a wedding': producing peer cultures in pretend play. Issue 3 (2nd September 2018) - Breathnach, Helen; Danby, Susan; O'Gorman, Lyndal
ABSTRACT: Play is valued pedagogically and conceptually as supporting children's imaginative capabilities and social development. In this article, we focus in particular on pretend play as a type of play activity in which children engage in the creative production and performance of peer cultures. In pretend play, new peer cultures are produced as children actively and creatively appropriate information from the adult world. Drawing on sociology of childhood understandings of children as agentic social actors, this ethnographic study with children aged five years in their first year of school in Queensland, Australia, explored children's production of peer cultures in their classroom play. We present here an extended pretend play episode in which children plan and perform a wedding framed in pretence and reality. Observations reveal the complexities of children's peer cultures, and ways in which they negotiate peer and adult agendas within the social structure of the classroom.